Promosi Upacara Adat Sekaten dan Grebeg Mulud sebagai Wisata Budaya di Surakarta - Dewanto, Yahya; Wahyuningrum, R. A. Heryani (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2017)
Sekaten and Grebeg Mulud ceremonies are held annually to commemorate the Prophet Muhammad SAW. These traditional ceremonies that have dynamic cultural complexity were the result of touches from foreign culture values, they have been held since Demak kingdom era and have long been included in the local government tourism calendar. Unfortunately, these ceremonies have not yet drawn the expected attention of domestic and foreign tourists. Appealing promotions are needed to make Sekaten and Grebeg Mulud known to public and become tourist destinations. The promotion design is using below the line media to disseminate information, whereas religious touch of Sekaten and Grebeg MuludSurakarta ceremonies is the positioning to promote these ceremonies as cultural tourism. The design is expected to create positive associations, revered and able to invite people to preserve these ceremonies as valuable cultural heritages.